Within and against the national doxa: on the historical emergence of (pro-)refugee politics in the Federal Republic of Germany, 1980-1993 - Pöggel, Tanita Jill (The University of Edinburgh, 2021)
The main purpose of this research project is to explore, examine and evaluate the largely forgotten early period of (pro-)Refugee activism between the late 1970s and early 1990s in the Federal Republic of Germany (FRG). My focus lies on the ambiguous positioning of Refugee actors and their supporters vis-à-vis the ‘national order of things’. Drawing on the theoretical works of Hannah Arendt and Pierre Bourdieu, I aim to strengthen the middle ground between approaches that focus on Refugees’ political exclusion and those that focus on the autonomous potential of Refugee protests. I therefore develop the argument that the symbolic power of the nation-state and its dominant political culture has a far- reaching impact on the political identities and agendas of Refugee actors and their supporters – including those who consider themselves radically oppositional. Based on extensive archival research in Germany and using methodological tools offered by critical discourse and frame analysis, I then trace and systematise the different ways in which (pro-)Refugee actors throughout the 1980s framed the (West) German state, the wider public audience, as well as other (pro-)Refugee actors. Moreover, I evaluate these framings in terms of the extent to which they reproduced orthodox narratives of German identity circulating in wider public discourse. Particular attention is paid to the usages of memory politics regarding Germany’s specific history of Nazism as a symbolic resource for critiquing the state and mobilising solidarity among the wider public audience. Overall, the empirical analysis demonstrates that all actors involved in pro-Refugee politics closely engaged with questions of national identity and collective memory to intervene in public debates about immigration and asylum. I show how they stood in an ambivalent relation to the national doxa which served simultaneously as negative and positive point of reference and which underpinned the growing conflicts over questions of (self-)representation at the turn of the decade.
Keywords: pro-refugee activism; Federal Republic of Germany; forced migration; national identity; memory politics; refugee activism; marginalisation